Texture and Chemical Properties of Two Depth Soils in a Toposequence of Anak Krakatau Before December 2018 Eruption - Astriana Rahmi Setiawati; Jamalam Lumbanraja; Septi Nurul Aini; Dermiyati Dermiyati; Henrie Buchari; Zuldadan Naspendra (UNIVERSITY OF LAMPUNG, 2020)
Anak Krakatau volcano is one of the famous volcanic mountains located in the sea to the south part of the Province of Lampung, Indonesia. The volcano was derived from the active Krakatau caldera that first appeared on the surface in 1930 or 47 years after the eruption of Krakatau in 1883. The materials produced by the Anak Krakatau eruption were very interesting related to soil forming materials, especially their physical and chemical properties. The objectives of this study were to present information about the texture and chemical properties of soil from Anak Krakatau Mountain taken at the southeast slope before the December 2018 eruption at two different depths. This study was conducted in March to September 2019 which consisted of two parts: (1) soil survey in the field and (2) soil analysis in the laboratory. Soil samples were taken from a toposequence at seven points with an interval about 15m above sea level (asl) on the southeast slope (approaching northeast) of the Anak Krakatau in July 2018 at the depth of 0-20 cm and 20-40 cm. The soil texture of Anak Krakatau mountain before eruption in December 2018 was sandy with the percentage of sand 98.82 - 99.59%; silt 0 - 0.59%; and clay 0.41 - 0.74%. The soil chemical properties of Anak Krakatau mountain were soil pH (H2O) 4.95 – 6.27; soil pH (KCl) 4.75 – 5.89; Cation Exchange Capacity 0.41 – 2.02 cmol(+) kg-1; Base Saturation 117.24 – 514.63%; CaO 2.63 – 6.34%; MgO 3.06 – 6.13%; K2O 0.019 – 0.034%; Na2O 0.035 – 0.080%; P-retention 82.10 – 84.74%; and organic carbon 0.06 – 0.72%. The SEM-EDX analysis showed that the amounts of Mg and Na were more than 1% and there were several trace elements present in Anak Krakatau soil, namely Sb (Stibium), Nb (Niobium), Y (Yttrium), F (Flour), Co (Cobalt), and Ba (Barium).